Analysis of audit findings of government agencies and public entities in Chile - Orostiga lazo, Valeria Andrea; Lillo Viedma, Felipe Eduardo; Lopez Flores, Vasco Tomas (Revista del CLAD Reforma y Democracia, 2025)
Government auditing is a process that strengthens the public integrity system, acting as an oversight mechanism on the use of public resources, for which different state entities are responsible. The research analyzes the recurrent patterns in the findings of audits carried out by the Comptroller General of the Republic of Chile during the period 2020 - 2023, by applying a mixed approach. From the quantitative perspective, a LDA language processing model is used, whose results are integrated with a qualitative analysis, interpreting the topics obtained through comparison with the literature and expert knowledge. Among the main findings, nine topics were found that address weaknesses associated with contracts and contracted services, institutional assets, accounting process, remunerations, accountabilities, field audits, food benefits, health residences, bank reconciliations. It is concluded that despite the existence of regulations governing the use of public resources, there is still a lack of actions to support their correct use and accountability by the responsible entities, as well as the application of corrective actions or sanctions for non-compliance with regulations, acting as a mechanism to promote administrative probity in the public interest.